The Influence of Sexual Orientation on the Perceived Fit of Male Applicants for Both Male- and Female-Typed Jobs - Clarke, Heather M.; Arnold, Kara A. (Frontiers in Psychology, 2018)
Research demonstrates the bias faced by individuals engaged in occupations that are perceived as inconsistent with their gender. The lack of fit model and role congruity theory explain how gender stereotypes give rise to the perception that an individual lacks the attributes necessary to be successful in a gender-incongruent job. Men employed in jobs traditionally held by women are perceived as wimpy and undeserving of respect. The majority of studies in this area have, however, failed to account for the sexual orientation of the individual being rated. Therefore, we carried out an experiment where 128 adults with experience in recruitment and selection, recruited through Qualtrics, rated heterosexual and gay male applicants applying for a gender-typed job. The heterosexual male was rated less effectual, less respect-worthy, and less hirable in the female-typed job condition than in the male-typed job condition. The gay male applicant, however, was rated similarly on all criteria across job gender-types, suggesting the gay male applicant was viewed as androgynous rather than high in femininity and low in masculinity as inferred by implicit inversion theory. The implications of these findings are discussed.